Senam Kaki untuk Penurunan Kadar Glukosa Darah pada Pasien Diabetes Melitus (Literatur Review) (Badan Riset dan Inovasi Nasional, 2024)
Background: Individuals afflicted with diabetes mellitus (DM) globally constitute 8.3% of the overall world population (IDF, 2015). Diabetes Mellitus manifests as a metabolic irregularity characterized by heightened blood sugar levels and disruptions in the metabolism of carbohydrates, fats, and proteins due to deficiencies in insulin secretion and function. Purpose: The aim of this literature review was to assess the influence of foot gymnastics exercises on individuals with diabetes mellitus. Methods: The literature exploration method involved utilizing Google Scholar (2020-2023) and employing the search terms